2001
DOI: 10.1136/heart.86.3.309
|View full text |Cite
|
Sign up to set email alerts
|

Four year follow up of aortic valve replacement for isolated aortic stenosis: a link between reduction in pressure overload, regression of left ventricular hypertrophy, and diastolic function

Abstract: Objective-To evaluate changes in left ventricular function and the impact of ventricular hypertrophy and pressure gradient early and late after aortic valve replacement in patients with isolated aortic stenosis. Design-41 patients with isolated aortic stenosis and normal systolic function underwent cross sectional and Doppler echocardiography two months before and two weeks and four years after aortic valve replacement. (96) ms (p < 0.05), remained improved. Prolonged isovolumic relaxation time was associated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
33
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 33 publications
8
33
0
1
Order By: Relevance
“…Similar benefits have also been observed after drug treatment in different animal models (3,30). Although reversal of LVH occurs after control of etiological factors, some studies have revealed incomplete reversal of pathophysiological changes, such as interstitial fibrosis, ventricular remodeling and dysfunction, and aberrant electrophysiology (2,3,12). Although numerous clinical and experimental studies have investigated effects of antihypertensive drugs (1,3), coronary structure and function (17,29), and alteration in gene expression (7,31,36) during reversal of LVH, the pathophysiological features and the time course of LVH regression are less clearly defined.…”
mentioning
confidence: 56%
See 1 more Smart Citation
“…Similar benefits have also been observed after drug treatment in different animal models (3,30). Although reversal of LVH occurs after control of etiological factors, some studies have revealed incomplete reversal of pathophysiological changes, such as interstitial fibrosis, ventricular remodeling and dysfunction, and aberrant electrophysiology (2,3,12). Although numerous clinical and experimental studies have investigated effects of antihypertensive drugs (1,3), coronary structure and function (17,29), and alteration in gene expression (7,31,36) during reversal of LVH, the pathophysiological features and the time course of LVH regression are less clearly defined.…”
mentioning
confidence: 56%
“…There has been clinical evidence that regression of LVH reduces morbidity and mortality and improves prognosis (9, 32). For example, antihypertensive treatment and aortic valvular replacement reverse LV structural, functional, and electrophysiological abnormalities (12,26,28). Similar benefits have also been observed after drug treatment in different animal models (3,30).…”
mentioning
confidence: 62%
“…LVMI is an index used in the evaluation of LVH. It is known that, LVMI decreases with the reduction of LV afterload after s-AVR and as a result, improvement in myocardial ischemia, functional capacity and long-term prognosis is observed [12,13]. The regression in LVMI after s-AVR is believed to be more important than valvular gradient as a prognostic factor [14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…DOE, dyspnea on exertion. remodeling [12][13][14], AS will lead to LV diastolic dysfunction, increased filling pressures, and heart failure (HF) symptoms.…”
Section: Asymptomatic Versus Symptomatic Asmentioning
confidence: 99%